The Influence of Fomo and Self-Control on Personal Financial Management With Impulsive Buying Behavior as a Mediating Variable Among Shopeepaylater User Students - May Ningsih; Nur Anita (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines how digitalization and social media intensification shape students’ financial behaviour by focusing on the psychological factors of Fear of Missing Out (FOMO) and Self-Control, which are presumed to influence Impulsive Buying Behaviour and, consequently, Personal Financial Management. Using a quantitative causal design, data were collected from 51 ShopeePayLater users in Bengkalis Regency and analysed through PLS-SEM using WarpPLS 7.0. The results indicate that FOMO does not significantly affect personal financial management but positively influences impulsive buying, whereas Self-Control positively affects financial management and negatively affects impulsive buying, making it a crucial stabilizing factor. Impulsive buying is found to negatively affect financial management and mediates the relationship between FOMO and financial outcomes, although it does not mediate the influence of Self-Control. These findings highlight the complex psychological mechanisms shaping students’ financial decisions in the BNPL era. The study provides theoretical contributions to behavioural finance and offers practical implications for educational institutions and BNPL providers to strengthen financial literacy, enhance students’ self-control, and reduce the behavioural risks associated with FOMO-driven consumption.